Enhanced photocurrent generation by photosynthetic bacterial reaction centers through molecular relays, light-harvesting complexes, and direct protein-gold interactions - den Hollander, Mart-Jan (Langmuir : the ACS journal of surfaces and colloids, 2011)
The utilization of proteins as nanodevices for solar cells, bioelectronics, and sensors generally necessitates the transfer of electrons to or from a conducting material. Here we report on efforts to maximize photocurrent generation by bacterial photosynthetic reaction center pigment-protein complexes (RCs) interfaced with a metal electrode. The possibility of adhering RCs to a bare gold electrode was investigated with a view to minimizing the distance for electron tunneling between the protein-embedded electron-transfer cofactors and the metal surface. Substantial photocurrents were achieved despite the absence of coating layers on the electrode or engineered linkers to achieve the oriented deposition of RCs on the surface. Comparison with SAM-covered gold electrodes indicating enhanced photocurrent densities was achieved because of the absence of an insulating layer between the photoactive pigments and the metal. Utilizing RCs surrounded by light-harvesting 1 complex resulted in higher photocurrents, surprisingly not due to enhanced photoabsorption but likely due to better surface coverage of uniformly oriented RC-LH1 complexes and the presence of a tetraheme cytochrome that could act as a connecting wire. The introduction of cytochrome-c (cyt-c) as a molecular relay also produced increases in current, probably by intercalating between the adhered RCs or RC-LH1 complexes and the electrode to mediate electron transfer. Varying the order in which components were introduced to the electrode indicated that dynamic rearrangements of RCs and cyt-c occurred at the bare metal surface. An upper limit for current generation could not be detected within the range of the illumination power available, with the maximum current density achieved by RC-LH1 complexes being on the order of 25 μA/cm(2). High currents could be generated consecutively for several hours or days under ambient conditions